Juridical And Sociological Review Of Animal Protection Law In Dog Meat Trade Cases In Sukoharjo Central Java Indonesia - Hane, Adrianus; Santoso, Aris Prio Agus; Habib, M.; Ferdinandez, Mariana Kresty; Franken, Karin Helga (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
In the use of animals by humans, over time there have been many function and there are principles that need to be considered in its use and handling. Animal abuse and animal abuse in Positive law have been regulated, regarding prohibitions against mistreating animals include Article 302 of the Criminal Code, Article 66 paragraph 2 of Law no.18 of 2009 concerning Amendments to Law Number 18 of 2009 concerning Animal Husbandry And Animal Health. Dog slaughterhouse activities where dogs are abused slaughtered and their meat traded for human consumption, in an unnatural way. The dog meat trade is an act that violates animal welfare. On In November 2021, problems regarding dog slaughterhouses were discovered in Dukuh Wirroragen, Kartasura District, Sukoharjo Regency. This research aims to find out the review criminal law regarding criminal acts of dog abuse and meat trafficking dogs at the slaughterhouse in Dukuh Wiroragen, Kartasura District, Sukoharjo Regency. In this research the author using a conceptual and comparative approach. The data source comes from primary data obtained through interviews with parties from the animal welfare activist coalition and the Police Sukoharjo. Secondary data in the form of primary legal materials in the form of the Criminal Code, Law no. 41 Years 2014 concerning Amendments to Law Number 18 of 2009 concerning Animal Husbandry and Animal Health. The results of this research show that: (1.) Criminal acts of abuse dogs at the slaughterhouse in Dukuh Wiroragen, Kartasura District, Sukoharjo Regency fulfills the elements and violates Article 302 paragraphs (1) and (2) of the Criminal Code, Article 66 paragraph 2 letters c, e, f and g Law of the Republic of Indonesia Number 41 of 2014 concerning Amendments Law Number 18 of 2009 concerning Animal Husbandry and Animal Health and Article 83 Paragraphs (1) and (2) Government Regulation Number 95 of 2012 concerning Public Health Veterinary and Animal Welfare. (2.) The dog meat trade contributes to and violates criminal threats to the law 18 of 2009 Article 89 paragraph 2 as amended and supplemented by Law number 41 of 2009 , 2014 concerning amendments to Law number 18 of 2009 jo. Article 55 paragraph (1) point 1, related entering animals from areas free from infected or suspected infected areas.